2015
DOI: 10.1523/jneurosci.1703-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Encoding of Vicarious Reward Prediction in Anterior Cingulate Cortex and Relationship with Trait Empathy

Abstract: Empathy-the capacity to understand and resonate with the experiences of others-can depend on the ability to predict when others are likely to receive rewards. However, although a plethora of research has examined the neural basis of predictions about the likelihood of receiving rewards ourselves, very little is known about the mechanisms that underpin variability in vicarious reward prediction. Human neuroimaging and nonhuman primate studies suggest that a subregion of the anterior cingulate cortex in the gyru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
144
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 108 publications
(148 citation statements)
references
References 45 publications
3
144
0
1
Order By: Relevance
“…This may seem surprising given that these regions have previously been implicated in empathy and/or social behavior (15,29,30,37). Although it is difficult to interpret a null finding, because there can be a number of reasons that a particular neural response is not observed, we note that in this experiment, participants were performing their task in a different reference frame (see refs.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This may seem surprising given that these regions have previously been implicated in empathy and/or social behavior (15,29,30,37). Although it is difficult to interpret a null finding, because there can be a number of reasons that a particular neural response is not observed, we note that in this experiment, participants were performing their task in a different reference frame (see refs.…”
Section: Discussionmentioning
confidence: 84%
“…Empathy, the capacity to vicariously experience and understand the affect of others (23)(24)(25)(26)(27), has been hypothesized to be a critical motivator of prosocial behaviors (25)(26)(27)(28). Previous studies have consistently shown that empathy can modulate neural responses to viewing others' pain (29) and viewing desirable outcomes (rewards) that will be delivered to others (15,30). Moreover, although empathy can be broken down into separable components associated with different social behaviors and traits (23,31,32), studies have suggested that both cognitive and affective aspects of empathic processing may motivate prosocial behaviors (33).…”
mentioning
confidence: 99%
“…However, there is evidence that the VMPFC and DMPFC regions differentially code between fair and unfair offers, including in studies where the magnitudes of offers to self and other were controlled for [see (Feng et al., 2015) for a meta‐analysis]. Studies that have directly compared activity to the same magnitude of rewards being delivered to self and other, find that activity in the VMPFC and DMPFC is not different between self and other rewards (Apps & Ramnani, 2014; Lockwood et al., 2015; Yoshida, Saito, Iriki, & Isoda, 2012). If activity in these regions is equally sensitive to payoffs to self and other, but is different to when these monetary values are unfairly divided, it suggests that the response in these regions is sensitive to the fairness of offers.…”
Section: Discussionmentioning
confidence: 99%
“…This includes evidence that the ACCg is sensitive to the predicted value of a reward another will receive, and also to the decisions others make about rewards, as well as the offers others make to us during the UG (Apps & Ramnani, 2014; Apps et al., 2015; Gabay et al., 2014; Lockwood et al., 2015). Whilst the design of this experiment was not optimized to look at how the brain processes the rewards received by others, the ACCg did respond differently to ingroup individuals compared to others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation